The Potential of Generative AI in Scientific Publishing: Exploration of Researchers’ Journeys from Draft to Publication - Alsulami, Meshari Rizqallah; Al-Hafdi, Fahad Saleem; Alhalafawy, Waleed Salim (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Recently, Generative AI (GenAI) has become one of the tools that can play a tangible role in bringing about fundamental transformations in the scientific publishing (SP) scene. Based on the necessary potential that GenAI offers, it has become necessary to conduct studies that explore the impact of these capabilities on the SP process. Consequently, this study aims to reveal how GenAI affects the stages of the SP process, starting from the preparation stage, through the submission and processing stage, and reaching the publication and dissemination stage, by studying the experiences of some researchers from the moment of writing the initial draft until reaching the final publication stage. This study implements a qualitative approach, depending on the phenomenological method to understand researchers’ subjective experiences with GenAI. Semi-structured interviews were conducted with eight researchers who were carefully selected according to criteria that confirm their research excellence and actual use of GenAI tools in their research. All interviews were conducted in a context that concentrated only on the ethical practices associated with the use of GenAI in SP. The results identified the potential of GenAI in three main axes of SP: (1) the preparation stage, (2) the processing and submission stage, and (3) the publication and dissemination stage. In the preparation stage, the results showed the role of GenAI in generating ideas, contributing to the development of research relationships, and helping to improve the quality of textual, digital, and graphic formulations. Regarding the submission and processing stage, the results showed the possibility of using GenAI as a GenAI editor to evaluate research before submission, select appropriate publication sources, and improve communication with editors and reviewers. Finally, in the publication and dissemination stage, the results showed the role of GenAI in increasing the dissemination of scientific knowledge by creating summaries in multiple languages and promotional content suitable for social media platforms and analyzing the impact of research after publication. The study provides recommendations for researchers, research institutions, and publishers to make the most of GenAI while keeping quality standards and scientific ethics.